Simuliid blackflies (Diptera: Simuliidae) and Ceratopogonid midges (Diptera: Ceratopogonidae) as vectors of Mansonella ozzardi (Nematoda: Onchocercidae) in northern Argentina - Shelley, A.J. (2001)
Mansonella ozzardi, a relatively non pathogenic filarial parasite of man in Latin America, is transmitted by either ceratopogonid midges or simuliid blackflies. In the only known focus of the disease in north-western Argentina the vectors have never been incriminated. This study investigated the potential vectors of M. ozzardi in this area. The only anthropophilic species of these Diptera families biting man at the time of the investigation were Simulium exiguum, S. dinellii, Culicoides lahillei and C. paraensis. Using experimentally infected flies S. exiguum and both species of Culicoides allowed full development of microfilariae to the infective stage, with C. lahillei being a more competent host than S. exiguum. Based on these data, biting rates and natural infectivity rates it is probable that at the begininning of the wet season C. lahillei is the main vector of M. ozzardi and both C. paraensis and S. exiguum secondary vectors. Additionally, it was found that a single dose of ivermectin was ineffectual in eradicating M. ozzardi from infected individuals in this area.